Infl uence of indole-3-butyric acid and triazole compounds on the photosynthetic pigments and biochemical constituents of Withania somnifera (L.) Dunal - R. Sridharan*, P. Sakthivel (Journal of Plant Stress Physiology, 2015)
Withania somnifera (L.) Dunal is popularly known as ashwagandha and also called Indian Ginseng and Winter Cherry. It is an important medicinal plant used in Indian System of Medicines like Ayurveda, Siddha, and Unani. The root of this plant has nutritional and medicinal values out of which health foods and herbal tonic are prepared. The root has high demand in pharmaceutical and nutraceutical industries so that it is essential to increase the root yield. This is new phenomenon to increase root yield as well as improve the biochemical constituents by using plant growth regulators. In the present investigation, the influence of indole-3-butyric acid (IBA) and triazole compounds viz., triadimefon (TDM) and propiconazole (PCZ) on the photosynthetic pigments and biochemical constituents of ashwagandha. Plants were treated with IBA 2.5 mg/L, TDM 20 mg/L, and PCZ 20 mg/L separately by soil drenching on 50, 90, and 130 days after sowing (DAS). Plants were analyzed randomly on 60, 100, and 140 DAS and it’s parameters like, photosynthetic pigments (total chlorophyll, carotenoids, anthocyanin, and xanthophylls) in leaf and biochemical constituents (starch, protein and amino acids) in leaf, stem and root organs of ashwagandha. It was determined that total chlorophyll, carotenoids, anthocyanin, and xanthophylls, starch, protein and amino acids content were increased in all the treatments. Among the treatments, triazole compounds showed beneficial due to the enhanced the photosynthetic pigments and increased biochemical contents higher level than followed by IBA treatment. From our results, it can be concluded that the triazole shows great significance application at low concentration could be a potential agronomical tool for successfully cultivation of this medicinally important root crops. Triazole compounds enhanced the photo-assimilate to shifting partition from leaves to roots and also alter mineral uptake and plant nutrition, This characters’ can be employed to satisfy needs of enhanced the photosynthetic pigments and biochemical constituents in ashwagandha.